Ambient Air Pollution and Helping Behavior: Evidence from the Streets in Beijing - Simon Chang; Ishita Chatterjee; Li Yu (Institute of Labor Economics (IZA), 2024)
We conducted a large-scale lost letter experiment with a novel design across all seasons in Beijing to study whether ambient air pollution influences helping behavior. We assessed air pollution by PM2.5 and PM10. Our novel design allowed us to collect real-time granular data from the streets. To mitigate endogeneity bias, we used the occurrence and intensity of thermal inversion as instrumental variables. We found that ambient air pollution increased the probability for a lost letter to be posted. Our finding suggests that when exposed to ambient air pollution, individuals may cope with the resulting adverse mental states by helping others.
Keywords: D9; Q5; 330; air pollution; helping behavior; particulate matter; thermal inversion; China